IMPACT OF SOCIO-ECONOMIC STATUS ON SPORTS INJURIES - Agarwal, Mukesh; Goel, Preeti; Goel, Anek (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Despite substantial statistical and infrastructural investments in sports, it is paradoxical that the status of our athletes remains terribly deficient in the country. A negligible investment is required for the athletes. An athlete’s fitness is fundamentally dependent on nutritional intake, suitable equipment, and the enforcement of safety measures. The economics of athletics clarifies the safety of athletes regarding injuries and physical fitness. The protective equipment is, in fact, somewhat costly. A nutritious diet is costly for an athlete from a middle-class family. A study was undertaken on the Sports Injury Centre, a part of Safdarjung Hospital in Delhi to analyze 50,768 patient records. Among these, 31,699 were non-athletes, while 19,069 were athletes from diverse sports disciplines. The results depicted that Approximately 50% of the injured athletes come from the disciplines of cricket, football, and athletics. The inadequate use of protective equipment, including shin guards, led to the injuries. The widespread popularity of cricket among the city’s residents will likely lead to a rise in cases. Protective equipment, including pads, gloves, and helmets, significantly impacts the occurrence of injuries. Athletics, being a rigorous activity, significantly depends on physical condition and a nutritious nutrition. The athletes generally originated from disadvantaged socio-economic situations, which may be the principal cause of their injuries.